Nitric oxide‐fixation by non‐symbiotic haemoglobin proteins in Arabidopsis thaliana under N‐limited conditions. (25th July 2016) - Kuruthukulangarakoola, Gitto Thomas; Zhang, Jiangli; Albert, Andreas; Winkler, Barbro; Lang, Hans; Buegger, Franz; Gaupels, Frank; Heller, Werner; Michalke, Bernhard; Sarioglu, Hakan; Schnitzler, Jörg‐Peter; Hebelstrup, Kim Henrik; et al.
Abstract: Nitric oxide (NO) is an important signalling molecule that is involved in many different physiological processes in plants. Here, we report about a NO‐fixing mechanism in Arabidopsis, which allows the fixation of atmospheric NO into nitrogen metabolism. We fumigated Arabidopsis plants cultivated in soil or as hydroponic cultures during the whole growing period with up to 3 ppmv of NO gas. Transcriptomic, proteomic and metabolomic analyses were used to identify non‐symbiotic haemoglobin proteins as key components of the NO‐fixing process. Overexpressing non‐symbiotic haemoglobin 1 or 2 genes resulted in fourfold higher nitrate levels in these plants compared with NO‐treated wild‐type. Correspondingly, rosettes size and weight, vegetative shoot thickness and seed yield were 25, 40, 30, and 50% higher, respectively, than in wild‐type plants. Fumigation with 250 ppbv 15 NO confirmed the importance of non‐symbiotic haemoglobin 1 and 2 for the NO‐fixation pathway, and we calculated a daily uptake for non‐symbiotic haemoglobin 2 overexpressing plants of 250 mg N/kg dry weight. This mechanism is probably important under conditions with limited N supply via the soil. Moreover, the plant‐based NO uptake lowers the concentration of insanitary atmospheric NOx, and in this context, NO‐fixation can be beneficial to air quality. Abstract : This study reports about a NO‐fixing mechanism in Arabidopsis, which allows the fixation of atmospheric NO into nitrogen metabolism. Non‐symbiotic haemoglobin class 1 and class 2 were identified as key proteins of the NO‐fixation pathway converting NO to nitrate, which is further introduced into the N‐metabolism. This mechanism is probably important under conditions with limited N supply via the soil. Moreover, the plant‐based NO uptake lowers the concentration of insanitary atmospheric NOx, and in this context, NO‐fixation can be beneficial to air quality.